Eosinophil infiltration, gastric juice and serum eosinophil cationic protein levels in Helicobacter pylori-associated chronic gastritis and gastric ulcer. Issue 5 (2004) - Aydemir, Selim; Tekin, Isak Ozel; Numanoglu, Gamze; Borazan, Ali; Ustundag, Yucel
Abstract : INTRODUCTION : Helicobacter pylori is one of the main causes of gastroduodenal diseases, such as chronic gastritis and peptic ulcer. It has been shown that eosinophils increase in the stomach in H. pylori infection. Eosinophilic cationic protein (ECP) is a cytotoxic molecule secreted by the activated eosinophils. However, there are no sufficient data about the role of ECP in H. pylori infection and its effect on ulcer development. In this study we investigated the gastric eosinophilic infiltration, gastric juice and serum ECP levels in patients with chronic gastritis and gastric ulcer associated with H. pylori . Materials and methods : Forty-four H. pylori -positive and 20 H. pylori -negative patients who underwent upper gastrointestinal system endoscopy after admitting with dyspeptic complaints were enrolled in the study. Twenty-one of the H. Pylori -positive patients had gastric ulcer while 23 patients had none. During endoscopy, multiple gastric biopsies and juices were taken. In gastric biopsies, H. pylori and eosinophilic infiltration were assessed. Additionally, gastric juice and serum ECP levels were measured. Results : Eosinophil infiltration, gastric juice ECP levels, and gastric juice/serum ECP ratios in the H. pylori -positive group were greater than in the H. pylori -negative group (p < 0.01 ). There was no statistically significant difference regarding serum ECP levels between the two groups (p > 0.05 ). When H. pylori -positive patients were compared with regard to gastric ulcer presence, however, there was no significant difference in gastric eosinophil infiltration, gastric juice ECP levels, serum ECP levels, and gastric juice/serum ECP ratios (p > 0.05 ). Conclusion : The results of this study suggest that eosinophils and eosinophil-released ECP may contribute to inflammatory changes seen in chronic gastritis, whereas there is no proof that they play a role in ulcer development.